Tableau 8 : the official guide - Peck, George (George E.) (McGraw-Hill Education, 2014)
Present a unified view of complex BI using the entire Tableau 8 toolkit Create and distribute dynamic, feature-rich data visualizations and highly interactive BI dashboards?quickly and easily! Tableau 8: The Official Guide provides the hands-on instruction and best practices you need to meet your business intelligence objectives and drive better decision making. Discover how to work from the Tableau GUI, load BI from disparate sources, drag and drop to analyze data, set up custom visualizations, and build robust dashboards. This practical guide shows you, step by step, how to design and publish meaningful business communications to end users across your enterprise. Navigate the Tableau user interface and data window Connect to spreadsheets, databases, and other sources Select data fields and drag them to desired screen locations Work with pre-defined visualizations and sample workbooks Display background maps and perform geographic analysis Add calculated fields, graphs, charts, tables, and statistics Combine multiple data sources into real-time dashboards Export your visualizations to the Web or in various file formats Electronic content includes: Videos that demonstrate the techniques presented in the book Sample Tableau workbooks.